Training for People Who Are Forgetful in Daily Life and to Improve Memory in Older People: Results of Effectiveness - Domínguez Orozco, María Eugenia (Pensando Psicología, 2015)
Introduction: Subjective complaints and forgetfulness in daily life among older people can be modified through cognitive training and mnemonic strategies and techniques to improve memory. Diverse methods and specific memory training programs have been developed in Spain with successful results from their implantation.Objectives: The main purpose of this article is to show the effectiveness of the training using different strategies and techniques for improving memory performance among older people. Specifically, trials were carried out with the association technique using faces and names, visualization and categorization strategies along with the loci method, all with older participants during a memory improvement workshop.Results and conclusions: The modular multifactorial design of the training and inclusion of these mnemonic procedures facilitated memory improvement. The analysis of the results showed a significant increase by means of training using prospective and retrospective tasks, such as “actions to be carried out in the morning”, and using the loci method, improvement in information codification through categorization, visual sensorial memory optimization using visualization, and finally, improvement of associative deficits in episodic memory in recalling people’s names.
Keywords: association and categorization; memory training; loci method; daily forgetfulness; visualization